Augmented Reality (AR) Based Science Learning Development Workshop to Improve ICT Literacy for Elementary School Teachers: Workshop Pengembangan Pembelajaran Sains Berbasis Augmented Reality (AR) untuk meningkatkan Literasi ICT Guru Sekolah Dasar - Rohman, Fatkhur; Yulianti, Dwi; Pramudianti, Pramudianti; Mona Adha, Mohammad; Setya Hermawan, Jody; Azzahra, Mia; Octi Pratiwi, Wulan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Industrial Revolution 4.0 demands that teachers master ICT literacy, but many teachers still have difficulty integrating technology into learning. This Community Service Program addresses this gap by conducting Augmented Reality (AR)-based training for 31 primary school teachers in the Teacher Working Group (TWG) of Primary School Region 6, Gedong Tataan District, Indonesia. The training was conducted in three stages: Preparation, Training, and Post-Training. The workshop results showed that AR integration significantly improves digital literacy, creativity, and the ability of teachers to develop interactive learning media. The teachers showed increased proficiency in using, creating, and integrating ICT-based learning materials, especially AR applications for science education. This initiative highlights the potential of AR technology in improving teacher competence and promoting innovative teaching strategies. These findings emphasise the importance of AR-based training in preparing educators to face the demands of 21st-century learning.